Optimal leniency programs when firms have cumulative and asymmetric evidence - Marc Blatter; Winand Emons; Silvio Sticher (University of Bern, Department of Economics, 2014)
An antitrust authority deters collusion using fines and a leniency program. Unlike in most of the earlier literature, our firms have imperfect cumulative evidence of the collusion. That is, cartel conviction is not automatic if one firm reports: reporting makes conviction only more likely, the more so, the more firms report. Furthermore, the evidence is distributed asymmetrically among firms. Asymmetry of the evidence can increase the cost of deterrence if the high-evidence firm chooses to remain silent. Minimum-evidence standards may counteract this effect. Under a marker system only one firm reports; this may increase the cost of deterrence.
Keywords: D43; K21; K42; L40; 330; antitrust; cartels; deterrence; leniency; evidence; Wettbewerbspolitik; Straffreiheit; Wettbewerbsbeschränkung; Strafe; Theorie